Legislating or rubber‐stamping? Assessing parliament's influence on law‐making with text reuse - GAVA, ROY; JAQUET, JULIEN M.; SCIARINI, PASCAL (European journal of political research, 2021)
Law‐making is a core function of parliaments in democratic systems. Yet, we still know little about the extent to which parliaments influence legislation and the reasons why MPs modify some bills more than others. We analyse the degree of bill amendments operated by parliament, by comparing bills before and after parliamentary deliberations with a text reuse approach. We postulate that MPs attempt to overcome the problem of limited processing capacity by prioritising certain bills over others. To this end, they use considerations related to institutional rules, attention dynamics and partisan politics. Empirically, we apply zero‐inflated beta regressions on a dataset covering about 1,700 bills adopted from 1995 to 2015 in the Swiss Parliament. Moreover, we address the problem of observational equivalence affecting analyses of parliament's impact on law‐making, by taking into account the government's anticipation strategy. Results highlight a reasonably high amendment activity, but with strong variations across bills. MPs change bills more if they are subject to direct democracy, rank high on the parliamentary agenda or if they attract media attention. The influence of the electoral cycle and coalition politics is not confirmed.